2014
DOI: 10.1074/jbc.m113.530626
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Stress-inducing Compounds Increase Osteoclast Formation in a Heat Shock Factor 1 Protein-dependent Manner

Abstract: Background: HSP90 inhibitors increase osteoclast formation and bone loss. Results: Altered Hsf1 activity impacts the ability of stress-inducing compounds to modulate osteoclast formation. Conclusion: Hsf1 plays an important role in stress-associated osteoclast formation, potentially via MITF. Significance: We identified a novel pathway whereby agents inducing stress can enhance osteoclast formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…Previous studies show that 17‐AAG‐dependent HSP90 inhibition leads to the transient activation of Src kinase and promotes osteoclastogenesis, resulting in promoted bone metastasis . This effect was also seen in other small molecule compounds that bind the N‐terminal ATPase domain of HSP90 and subsequently induce a heat shock response via heat shock transcription factor 1 (HSF1) . Unlike transforming growth factor‐beta (TGF‐β), HSP90 inhibitors stimulate the late phase of osteoclast differentiation in the presence of receptor activator of nuclear factor kappa‐B ligand (RANKL) .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies show that 17‐AAG‐dependent HSP90 inhibition leads to the transient activation of Src kinase and promotes osteoclastogenesis, resulting in promoted bone metastasis . This effect was also seen in other small molecule compounds that bind the N‐terminal ATPase domain of HSP90 and subsequently induce a heat shock response via heat shock transcription factor 1 (HSF1) . Unlike transforming growth factor‐beta (TGF‐β), HSP90 inhibitors stimulate the late phase of osteoclast differentiation in the presence of receptor activator of nuclear factor kappa‐B ligand (RANKL) .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the use of HSP90 inhibitors in tumors associated with bone lesions is actually controversial. Contradictory reports suggested that blocking HSP90 inhibits both primary tumor growth and bone metastases (13,24), while other recent studies have reported that HSP90 inhibition using 17-AAG promotes prostate and breast cancer growth in bone by inducing both osteoclast differentiation and activation via induction of Src signaling or HSF1-dependent mechanism (14,15,46). These results highlight a potential risk to use HSP90 inhibitors therapies in patients with tumor-associated bone lesions.…”
Section: Discussionmentioning
confidence: 67%
“…NFATc1 activation is required for the induction of essential osteoclast transcription factors, such as microphthalmia-associated transcription factor (MITF) (44). In addition to the NFATc1-MITF pathway, MITF is upregulated by HSP70 (44). Although 17-AAG is a known potent cytotoxic drug, it is associated with side effects that cause bone loss due to increases in HSP70-MITF.…”
Section: The Effects Of Calcineurin Inhibition On Apoptosis and Prolimentioning
confidence: 99%
“…PPP3CA protein levels, but not mRNA expression, decreased in differentiated osteoclasts treated with panobinostat ( Figure 6B). NFATc1 activation is required for the induction of essential osteoclast transcription factors, such as microphthalmia-associated transcription factor (MITF) (44). In addition to the NFATc1-MITF pathway, MITF is upregulated by HSP70 (44).…”
Section: The Effects Of Calcineurin Inhibition On Apoptosis and Prolimentioning
confidence: 99%